Astragalus aytatchii (Fabaceae), a new species from Anatolia, Turkey - Akan, H; Civelek, S (Finnish Zoological Botanical Publishing Board, 2001)
Astragalus aytatchii Akan & Civelek sp. nova (Fabaceae) from middle Anatolia, Turkey, is described and illustrated in line drawings. It is compared with the closely related A. elatus Boiss & Bal. Both species belong to Astragalus sect. Alopecuroidei DC. (= Alopecias Bunge).
Keywords: Astragalus; Fabaceae; taxonomy